Avaliação imunohistoquímica do estresse oxidativo no sistema nervoso central de cães positivos para cinomose - Viscone, Érica Almeida (2020)
Canine Distemper is a disease caused by Canine morbillivirus (CM), a pantropic pathogen that can affect the Central Nervous System (CNS) causing demyelination. However, the pathogenesis of this lesion remains to be clarified. CNS fragments were submitted to RT-PCR for partial detection of the gene that encodes the CM nucleoprotein; anti-CM immunohistochemistry to locate viral proteins in the tissue and anti-4-hydroxynonenal immunohistochemistry (4-HNE) as a marker of lipid peroxidation product. Through the results, it was observed that the demyelinated area was positive for the presence of viral proteins and cells immunostained for 4-HNE. The results showed the presence of virus proteins in the demyelinated area with the presence of 4-HNE. Considering these results, we strongly believe that the virus’ presence causes oxidative stress leading to lipid peroxidation, which causes tissue damage and results in demyelination. In conclusion, oxidative stress plays an important role in canine distemper pathogenesis.